DETERMINATION OF SUSPECT TOWARD WITNESS THAT PROVIDED INFORMATION IN CRIMINAL TRIALS: EXPANSION OF THE AUTHORITY OF JUDGES - Ramadhanty, Ratu Ayu; Saragih, Yasmirah Mandasari; Marbun, Rocky (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2023)
This research is based on the power of the judiciary through the implementation of the main functions and duties of the judge to resolve a case submitted to him as well as to uphold the law and provide justice. The method used in this research is normative legal research with data sources obtained from primary legal materials, namely laws and regulations and secondary legal materials, namely books, legal journals, results of scientific research, and opinions of experts. The data obtained was then processed and analyzed using a qualitative descriptive method, namely by describing the data in the form of regular, coherent, logical, and effective sentences so as to facilitate understanding and interpretation of the data and describing the data in the form of sentence descriptions. The results of the study show that the Criminal Procedure Code has been perfected by the existence of the Constitutional Court Decision Number 21/PUU-XII/2014 which explains that the conditions for determining a suspect must be based on at least 2 (two) pieces of evidence as stipulated in Article 184 of the Criminal Procedure Code and accompanied by an examination of potential suspects.